The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/met11040593
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure, Residual Stresses, and Strain-Rate-Dependent Deformation and Fracture Behavior of AISI 304L Joints Brazed with NiCrSiB Filler Metals

Abstract: The knowledge of alloy–process–structure–property relationships is of particular interest for several safety-critical brazed components and requires a detailed characterization. Thus, three different nickel-based brazing filler metals were produced with varying chromium and molybdenum content and were used to braze butt joints of the austenitic stainless steel AISI 304L under vacuum. Two holding times were used to evaluate diffusion-related differences, resulting in six specimen variations. Significant microst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…In addition to the characterization of the brazed seam, investigations on the final cubic ceramic head with the titanium insert are required in the next steps in order to verify, for example, the damping properties of the titanium insert, as already shown by simulation [27]. For this purpose, digital image correlation (DIC) or local strain measurements with strain gauges should be used, as already shown in combination for brazed steel joints in [28]. For further qualification of the brazed joints for use in the human body, biocompatibility tests are essential.…”
Section: Futher Investigationsmentioning
confidence: 99%
“…In addition to the characterization of the brazed seam, investigations on the final cubic ceramic head with the titanium insert are required in the next steps in order to verify, for example, the damping properties of the titanium insert, as already shown by simulation [27]. For this purpose, digital image correlation (DIC) or local strain measurements with strain gauges should be used, as already shown in combination for brazed steel joints in [28]. For further qualification of the brazed joints for use in the human body, biocompatibility tests are essential.…”
Section: Futher Investigationsmentioning
confidence: 99%
“…Abdolvan [14] designed a new fixture for the shear test of SAF 2507 and AISI 304 dissimilarmaterial brazing joints. Otto JL et al [15] used three different nickel-based brazing filler to brazing joints of AISI 304L under vacuum and then carried out tensile tests at low and high strain rates to evaluate the strain-rate-dependent tensile strength of the brazing joints. It was found that high strain rates increased the ultimate tensile strength of all variations and shifted the other mechanical properties in the high-speed tensile tests.…”
Section: Introductionmentioning
confidence: 99%